Axillary lymph node status, age at presentation and menopausal status in female breast cancer patients attending a government tertiary care teaching hospital in Mysore, Karnataka, India - S., Chandrashekar; V. L., Ajith; A., Ashwin Raghavendra (International Surgery Journal, 2017)
Background: Breast cancer is now the leading cause of cancer among Indian women. This study was aimed at creating a database of female breast cancer patients with emphasis on age, menopausal and axillary lymph node metastasis. Methods: A retrospective study was conducted among 103 female breast carcinoma patients who sought treatment in the Department of General Surgery from 2016 January to December. Various data including age at presentation, menopausal status, lymph node status, grade of the tumor, family history of breast cancer, location, size of the tumor and histopathological types were studied. Results: Mean age of the study population was 52.7years. Of the 103 patients, 70.9% were post-menopausal. Among different clinical and pathological variables, Grade of the tumor and menopausal status were showing statistically significant association with positive axillary lymph nodal status. Conclusions: The variables which are predictive of axillary lymph node involvement in breast cancer are tumour grade and menopausal status. The current data may be used to tailor the management protocol of patients with breast carcinoma in this region of the country.